Perilaku Produsen dalam Perspektif Islam: Integrasi Maqashid al-Syari’ah dan Praktik Bisnis Halal Berkelanjutan - Fawaz Irfan Mubarok; Oki Khairul Hikmah; Rizka Rahmayani (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze producer behavior from an Islamic perspective by integrating the principles of maqashid al-shari’ah with the demands of sustainable halal business practices. The study employs a qualitative approach using library research. Data were obtained from the Qur’an, Hadith, classical and contemporary Islamic economic literature, and relevant scholarly articles, and were analyzed using content analysis through the stages of identification, reduction, categorization, interpretation, and synthesis of concepts and previous research findings. The findings show that Islamic producer behavior goes beyond normative halal compliance and represents an integration of tawhid, khalifah, maqashid al-shari’ah, justice, trustworthiness, and ihsan throughout the production process. These principles are translated into concrete practices through halal and tayyib standards, supply-chain transparency and traceability, consumer and worker protection, social responsibility, and sustainable environmental management. The novelty of this study lies in developing a conceptual framework that positions producers simultaneously as economic, moral, and development agents, with maqashid al-shari’ah serving as the orientation for evaluating production behavior. This framework extends the understanding of Islamic producer behavior from a focus on sharia compliance toward a production model that integrates economic efficiency, social welfare, environmental sustainability, and spiritual objectives